The Effect of Organizational Communication, Innovative Work Behavior, and Work Motivation on the Performance of Guidance and Counseling Teachers - Tim Slamet Sulistiyono; Mokhamad Natsir; Harianto Respati (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The objective of this study is to examine the effect of communication, innovative behavior, and work motivation on teacher performance. This research focuses on investigating the performance of Guidance and Counseling teachers at public junior high schools in Magetan Regency. This study employs a quantitative research design using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) statistical analysis technique. The population of this study consists of 97 respondents, and a census method was applied. The respondents are Guidance and Counseling teachers with a teaching tenure ranging from 0 to 36 years. The findings of this study indicate that communication, innovative behavior, and work motivation have a significant effect, both partially and simultaneously, on the performance of Guidance and Counseling teachers at SMP Negeri in Magetan Regency, with work motivation emerging as the most dominant variable. These results confirm that the improvement of Guidance and Counseling teachers’ performance is strongly determined by the quality of communication, innovative capacity, and strong work motivation in carrying out counseling service duties. The results of this study are expected to serve as consideration and input for the Education Office, school supervisors, and school principals in implementing continuous professional development for Guidance and Counseling teachers in order to enhance the quality of school services.